LEARNING A LANGUAGE AS AN ADULT - Eshmirzaeva , Nozima Bakhodirovna (Educational Research in Universal Sciences, 2023)
In contrast to childhood, learning can be highly challenging for adults. Yet the rewards for those who do learn second or third,or fourth. language are profound: increased travel opportunities, of course, but also improved memory, focus, and ability to multitask. Bilingual brains are better shielded against cognitive disorders such as “Alzheimer’s” disease and according to a poll conducted by the language app Babel, knowing multiple languages can make you seem more attractive. In the following you will find out that contrary to convention thinking, it isn’t too late.